Menjembatani Penelitian Kualitatif dan Kuantitatif Irfan Sanusi - Sanusi, Irfan (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2009)
The quantitative method of research inspired by August Comte in his Philosophy of Positivism, is contradictory with the qualitative method of research which is one of the methods elaborated and derived fromÂ rationalism. I suggest that quantitative researchÂ modelsâ descriptive model, correlation, experiment and quasi-experiment â should be placed on the grand theory as well as the the social context, or to follow the logic of qualitative method, so thatÂ research invention is inseparable from the grand situation. In light of this view, IÂ suggest that theÂ two contradictory methods of research be combined.